(untitled) - Riches, John; (1939-...) (New York, USA, 1982)
By explicating and evaluating Jesus' use of the language of Judaism in new contexts, John Riches is able to show how the preaching of the Kingdom transformed the meaning of God's rule.
Keywords: Jesus Christ -- Relation to Judaism